Analisa Kedataran Guide Ways Terhadap Pengaruh Gerak Carriage Pada Mesin Bubut G.D.W. LZ 350 Dengan Alat Ukur Digi-Pas DWL-200 - Arief, Dodi Sofyan; Arif, Muhammad; Syafri, Syafri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
The lathe is a machine tool used to cut cylindrical workpieces. On the lathe, the direction of tailstock movement follows the surface contour board machine guide ways. If there is uniformity flatness on the bottom of the machine, it will affect the precision of the lathe. The purpose of this study is to determine and evaluate the flatness deviation value in guide ways of lathes GDW LZ 350. The method used is to measure the guide ways on a lathe using a measuring instrument digi-pas DWL-200, to obtain a deviation value as a reference process leveling machine pedestal. Results obtained from this study is a guide ways flatness deviation average value of 0,1o, general flatness deviation occurs at both ends of the guide ways, the machine MB3 and MB4 flatness deviation occurs is not uniform between the guide way 1 and 2, it caused by the tilt position of guide ways. So loading guide ways only focused on one side only.Keywords : lathe, guide ways, flatness, pedestal